2023
DOI: 10.1227/neu.0000000000002538
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Progression-Free Survival in Patients With Spinal Intramedullary Ependymoma: A Multicenter Retrospective Study by the Neurospinal Society of Japan

Abstract: BACKGROUND AND OBJECTIVES: Ependymoma is the most common spinal intramedullary tumor. Although clinical outcomes have been described in the literature, most of the reports were based on limited numbers of cases or been confined to institutional experience. The objective of this study was to analyze more detailed characteristics of spinal intramedullary ependymoma (SIE) and provide clinical factors associated with progression-free survival (PFS). METHODS: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…An extensive body of literature exists investigating clinical and treatment characteristics that portend improvements in overall survival (OS) and progression-free survival (PFS) metrics in spinal ependymoma patients [ 2 , 4 , 5 , 7 15 ]. Furthermore, a number of authors have demonstrated the benefits of gross total resection (GTR) over subtotal resection (STR) as a principal treatment for spinal ependymomas using both OS and PFS as primary outcome criteria [ 4 , 7 , 9 , 15 ]. Abdel-Wahab et al conducted one of the largest retrospective reviews of 120 spinal ependymoma patients undergoing primary surgical treatment with or without adjuvant radiation from 1953 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…An extensive body of literature exists investigating clinical and treatment characteristics that portend improvements in overall survival (OS) and progression-free survival (PFS) metrics in spinal ependymoma patients [ 2 , 4 , 5 , 7 15 ]. Furthermore, a number of authors have demonstrated the benefits of gross total resection (GTR) over subtotal resection (STR) as a principal treatment for spinal ependymomas using both OS and PFS as primary outcome criteria [ 4 , 7 , 9 , 15 ]. Abdel-Wahab et al conducted one of the largest retrospective reviews of 120 spinal ependymoma patients undergoing primary surgical treatment with or without adjuvant radiation from 1953 to 2000.…”
Section: Introductionmentioning
confidence: 99%
“…We eagerly read the recent publication by Naito et al 1 Although ependymomas are the most common spinal intramedullary tumor, previous studies outlining disease progression and functional outcomes after treatment have been limited in case numbers and also biased by the inclusion of nonintramedullary subtypes. Naito et al performed a retrospective multicenter study with more exclusive histological inclusion criteria as well as a large sample size to attain a more complete analysis on the predictors of progression-free survival and functional outcomes in spinal intramedullary ependymoma (SIE) treatment.…”
mentioning
confidence: 99%
“…We are also well aware of their importance. However, because this study 2 is retrospective observational multicenter analysis, it is true that there are many research limitations for tumor characteristics, tumor axial location, operative variables, intraoperative neuromonitoring, and gene analysis. Of course, we also understand that more detailed analysis is ideal, especially for gene analysis.…”
mentioning
confidence: 99%